Elucidating the food web structure of the subterranean invertebrate communities of arid zone Western Australia - Sacco, Mattia; Blyth, alison; Humphreys, William; Laini, Alex; Hua, Quan; Grice, Kliti (2018)
Groundwater forms over 95% of liquid freshwater, and is the primary water source for many arid and semi-arid regions. However, the ecology of aquifers is poorly understood, despite groundwater fauna being proposed as regulating water quality via consumption of organics and microbes. A key obstacle is the inaccessibility of these ecosystems and their microinvertebrate fauna, limiting feasibility of conventional ecological techniques. To address this problem, we apply a suite of chemical tools to reconstruct key ecosystem functions – stable isotopic analysis of δ13C and δ15N in single amino acids, and radiocarbon analysis of faunal groups. Compound specific stable isotope analysis of δ13C and δ15N separates the source isotopic signal from the signal generated by trophic enrichment. δ15N analysis allows calculation of relative trophic position, while our δ13C data shows clear distinctions between consumers of plant material, and generalists grazing on a range of organics. By combining stable isotope techniques with radiocarbon analysis, which characterises proportions of fresh, recycled, and geological carbon, we can: i) Assign trophic position to different invertebrate species, ii) Identify the dominant carbon sources at the base of the subterranean food web, iii) Assess changes in these characteristics with fluctuations in physiochemical parameters. This data will allow much improved characterisation of subterranean ecosystem function, and when combined with taxonomic and DNA research, will provide a comprehensive toolkit to assess system resilience under natural and anthropogenic pressures.